Mewujudkan Lingkungan yang Bersih, Sehat, dan Aman melalui Edukasi dan Gotong Royong - Pratama, Anggit Septian; Karmana, I Wayan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this service activity is to create a clean, healthy and safe environment through education and mutual cooperation. The service methods that have been carried out are: 1) conducting interviews and observations with partners regarding the problems and conditions of the Dayan Mosque Environment, Pancor Village, Selong District, East Lombok Regency; 2) post pamphlets about keeping clean; 3) mutual cooperation in environmental cleanliness, especially in places of worship; 4) put up banners in areas where masks are mandatory; and 5) spraying disinfectant in places of worship and schools. The results achieved from this service activity are that the community responds well to the activities carried out, for example some young people or teenagers always wear masks when going outside the house, some people are aware of the environment and no longer throw rubbish carelessly in the gutter. Through effective education, people can understand the importance of maintaining a clean and healthy environment. Apart from that, the implementation of mutual cooperation as a form of collaboration in cleaning the environment strengthens the sense of togetherness and shared responsibility.